Perception, justification, and identity: Kumārila’s theory of universals in the Ākṛtivāda chapter of the Ślokavārttika - Ye, AX (2023)
This thesis examines the theory of universals expounded by the seventh century Mīmāṃsā philosopher, Kumārilabhaṭṭa, in the Ākṛtivāda chapter of his magnum opus, the Ślokavārttika. Kumārila’s innovative conception of universals constitutes an important chapter in the history of Indian philosophy. Through a close reading and philosophical analysis of the text, I argue that Kumārila provides a sophisticated epistemological framework for his theory of universals and makes daring propositions about the ontology of universals in the Ākṛtivāda. Ultimately, I aim to show that it is Kumārila’s epistemological arguments for universals that underpin his contention that universals are real existences and that universals and particulars share a certain level of identity. My approach to study the Ākṛtivāda in this thesis is twofold. My first objective of is to present what Kumārila’s theory of universals entails and how he expounds his theory of universals in the Ākṛtivāda. My second objective is to understand the transmission and critical reception of Kumārila’s theory of universals in a historical context. To achieve the first goal, I prepare a new edition of the Ākṛtivāda in Chapter 2 by using four published editions and five manuscripts, and then I provide an annotated translation of the Ākṛtivāda in Chapter 3. The second goal is met by the- analytical chapters of this thesis (Chapter 4-6), with each chapter showcasing how Buddhist, Jaina, and Vedānta philosophers engage with Kumārila’s theory of universals, respectively. Given that Kumārila’s theory of universals was composed at a time in which Indian inter-religious debate regarding metaphysics and epistemology reached a new stage, I argue that the legacy of Kumārila’s theory of universals must be viewed in context of that inter-religious debate. As a result, each of the analytical chapters will address the impact of Kumārila’s theory on different philosophical traditions in classical India: in Chapter 4, I will consider the effect on the Buddhist logico-epistemological school, in Chapter 5, the effect on Jaina philosophers, and finally in Chapter 6, the effect on the non-Mīmāṃsā Brahmanical tradition.